Identification and antimicrobial activity of micromonospora strains isolated from Coto island’s sediments - Hong Minh, Le Thi; Quyen, Vu Thi; Thu Huyen, Vu Thi; Kim Cuc, Nguyen Thi; Cuong, Pham Van; Dao, Phi Thi; Vinh, Le Cong; Mai Huong, Doan Thi; Cuong, Pham Viet (Vietnam Journal of Chemistry, 2016)
Three actinomycete strains G043, G047, G068 were isolated from marine sediments of Co To island, Thanh Lan, Vietnam. These strains were cultivated in ISP2 medium. The fermentation broths were extracted three times with ethyl acetate then the extracts were evaporated under reduced pressure to yield crude extracts. Quantitative assay was used to determine MIC of extract against some reference bacteria. The result revealed that most of the isolates were active against Enterococus faecalis ATCC 13124 with MICG043 = 64 µg/ml, MICG047= 256 µg/ml, MICG068 = 256 µg/ml and Candida albican ATCC1023 with MICG043 = 16 µg/ml, MICG047 = 4 µg/ml, MICG068 = 2 µg/ml. Moreover, two strains G043 and G047 showed strong inhibition on the growth of Bacillus cereus ATCC13245 with MICG043 = 32 µg/ml, MICG047 = 128 µg/ml. These actinomycetes isolates were subjected to morphological, physiological and biochemical analyses and phylogenetic investigation based on 16S rRNA gene sequences. The obtained results showed that all actinomycete isolates belonged to genus Micromonospora. Strains G043 and G047 were identified as Micromonospora aurantiaca, G068 was identified as Micromonospora chalcea. Keywords. Actinomycetes, Micromonospora, Antimicrobial activity, MIC, 16S rRNA gene sequences.